A Review of Color Breakup Assessment for Field Sequential Color Display. Issue 2 (26th March 2019) - Qin, Zong; Zhang, Yuning; Lin, Fang‐Cheng; Huang, Yi‐Pai; Shieh, Han‐Ping D.
Abstract: Assessing color breakup is a prevalent and intrinsic issue in field sequential color displays. Here, the authors review selected works on the topic, including studies on threshold display configurations for perceptible color breakup, metrics for special patterns, and metrics for natural images with varying contents.